PROGRAM SANISCARA MAPRANI SEBAGAI MEDIA MENUMBUH KEMBANGKAN KARAKTER SISWADI SMP NEGERI 1 BANGLI - Gama, Putu Gede (JAPAM (Jurnal Pendidikan Agama), 2025)
Character education is one of the important aspects of the education system in Indonesia. Inthe era of globalization, where cultural and ethical values are often eroded by the unstoppable flowof information, character education becomes very relevant to form a person of excellence andintegrity. One of the programs at SMP Negeri 1 Bangli that can be implemented as a medium fordeveloping student character is the Saniscara Maprani program. This study aims to obtain accurateinformation and an objective picture of the Saniscara Maprani program. The data collection methodsused are: observation, interviews, literature studies and documentation studies. The data wereanalyzed using qualitative descriptive analysis method. The results showed (1) The implementationof the Saniscara Maprani program is the preparation, implementation and evaluation of theSaniscara Maprani program (2) The function of the Saniscara Maprani program is as an expressionof gratitude to Sang Hyang Widhi Wasa, maintaining harmonious relationships among the extendedfamily of SMP Negeri 1 Bangli, for the formation of student character and for the formation of apositive school culture. (3) The implications of the Saniscara Maprani program are: the growth ofstudents' character, increasing students' awareness to carry out their religious teachings, increasingstudents' concern for the environment, creating a positive school culture and creating good characterof students in the school and community environment.